INTEGRATING GEOGEBRA IN LEARNING RIGHT TRIANGLE GEOMETRY:A DESCRIPTIVE STUDY OF FIRST-YEAR UNIVERSITY STUDENTS’ RESPONSES - Sianturi, Agustina; Ningsih, Yunika Lestaria (Perpendicular : Journal of Mathematics Education and Learning, 2025)
The rapid development of digital technology has significantly influenced instructional practices in mathematics education, particularly in the teaching of abstract and conceptually demanding topics such as geometry and trigonometry. One foundational topic that frequently presents learning challenges is right triangle geometry, which underpins students’ understanding of trigonometric ratios and their applications. This study aims to describe university students’ responses to the use of GeoGebra as a technology-assisted learning tool in right triangle geometry instruction. Employing a descriptive survey research design, the study involved 30 first-year students enrolled in a Mathematics Education program at Universitas PGRI Palembang. Data were collected through a structured student response questionnaire administered after a GeoGebra-assisted learning session. The questionnaire examined four aspects: perceived conceptual understanding, learning motivation, interactivity, and ease of problem solving. Data were analyzed using descriptive statistics in the form of percentage distributions. The findings indicate that students demonstrated positive to very positive responses across all assessed aspects, particularly in learning motivation and perceived conceptual clarity supported by visual representations. While the results do not claim instructional effectiveness or learning gains, they suggest that GeoGebra is perceived as a supportive and engaging tool for learning right triangle geometry. The study contributes descriptive evidence regarding students’ perceptions of GeoGebra-based instruction and provides pedagogical insights for mathematics educators integrating digital tools in geometry learning.